Pengaruh Efektivitas Sistem Informasi Akuntansi Terhadap Kinerja Karyawan Dengan Budaya Organisasi Sebagai Variabel Moderasi - Dwi Cahyanti, I Gusti Ayu; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 23 No 3 (2018)DO - 10.24843/EJA.2018.v23.i03.p18, 2018)
This study was conducted to determine the effect of effectiveness of accounting information systems on employee performance and the influence of moderation of organizational culture in the relationship between the effectiveness of accounting information systems with employee performance. The research method used is quantitative approach in the form of associative. This research was conducted in Public Relations Bureau and Protocol of Regional Secretariat of Bali Province. In this research used sampling method with saturated sampling which means sampling in which all members are sampled. Analytical technique used is moderation regression technique through interaction test. Questionnaire retrieval in this research as much as 45. The research data meets the requirement of classical assumption test and fit model test with adjusted R 2 equal to 50,8%. The result of research shows that the effectiveness of accounting information system has a positive effect on employee performance, organizational culture have positive effect on employee performance, and organizational culture can moderate influence effectiveness of accounting information system to employee performance. Keywords: effectiveness of accounting information system, organizational culture, work performance